Forged products by Russian craftsmen of the 17th–19th centuries on the basis of materials from the Kikki-Akki burial ground of Upper Taz Selkups: technological characteristics - N.M. Zinyakov (Вестник археологии, антропологии и этнографии, 2020)
The article studies the technology of making iron and steel items of Russian origin, discovered in the Kikki-Akki burial ground of Northern Selkups (18th–19th centuries) in the north of Western Siberia in the upper reaches of the Taz River. In the study, we established the origin and chronology of Russian industrial goods in Western Siberia, as well as factors under the influence of which they appeared among the indigenous Siberian population. We examined knives and axes (17th — early 19th centuries) using the methods of metallographic analysis includ-ing macro- and micrographic examination, as well as microhardness testing. They provide an opportunity to de-termine the structure of the metal, which in turn helps determine chemical composition, physical and mechanical properties of the product. The analysis of forged products revealed that they were made according to the techno-logical traditions of Russian metalworking production existing in the 17th — early 19th centuries. Its distinctive features included the development and widespread practice in applying the modifications of two technological schemes for producing items from ferrous metal. The former was based on the welding either of iron and steel or of different grades of steel, whereas the latter involved all-steel structures. The former technological scheme pre-dominated in the production of items found in the Kikki-Akki burial ground. Moreover, the production of welded structures lacked standardisation. The following techniques were used in the production of knives: two-layer wel-ding of iron and steel, three-layer welding, V-joint welding, oblique welding, built-up welding at the ends and wel-ding of the steel blade. The use of soft quenching was noted as an additional operation that improved the opera-tional properties of the household tool. This variety of used technological schemes reflects the complex nature of the formation of the industrial goods market in Western Siberia. The selection of items made using different welded technologies is associated with the intention to use metal products of the highest quality for the fur trade and yasak collection. However, all-metal structures predominated in the main centres for the production of forged goods — cities of European Russia and Western Siberia.